The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1007/s12094-015-1424-6
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Cathepsin L is associated with gefitinib resistance in non-small cell lung cancer

Abstract: Lung cancer, the most common malignancy, is still the leading cause of cancer-related death worldwide. Non-small-cell lung cancer (NSCLC) accounts for 80 % of all lung cancers. Recent studies showed Cathepsin L (CTSL) is overexpressed in various cancerous tissues; however, the association between CTSL expression and EGFR-TKI resistance remains unknown. In this study, we investigated the expression of CTSL in lung cancer specimens and matched normal tissues by quantitative real-time PCR and IHC. The functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Zheng et al revealed that CTSL inhibition enhances the availability of cytoplasmic and nuclear protein drug targets, including estrogen receptor-α, Bcr-Abl, topoisomerase-IIα, histone deacetylase 1, and androgen receptor [9] . CTSL suppression also improves gefitinib resistance in non-small cell lung cancer [14] , and CTSL knockdown can increase the sensitivity of ovarian cancer cells to paclitaxel [38] . Our previous study also suggested that CTSL may be a novel therapeutic target to prevent tumor cells from becoming resistant to chemotherapy and to reinforce the efficiency of paclitaxel and cisplatin against lung cancer [12] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zheng et al revealed that CTSL inhibition enhances the availability of cytoplasmic and nuclear protein drug targets, including estrogen receptor-α, Bcr-Abl, topoisomerase-IIα, histone deacetylase 1, and androgen receptor [9] . CTSL suppression also improves gefitinib resistance in non-small cell lung cancer [14] , and CTSL knockdown can increase the sensitivity of ovarian cancer cells to paclitaxel [38] . Our previous study also suggested that CTSL may be a novel therapeutic target to prevent tumor cells from becoming resistant to chemotherapy and to reinforce the efficiency of paclitaxel and cisplatin against lung cancer [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Then we indicated that CTSL also regulates drug resistance by mediating EMT through its effects on the expression of EMT-associated transcription factors, Snail, Slug, ZEB1, and ZEB2 [12] . The overexpression of CTSL is associated with the chemoresistance and invasion of epithelial ovarian cancer [13] and is related to gefitinib resistance in lung cancer [14] . Increased CTSL levels are associated with the increased chemoresistance of tumor cells and may be applied to gene therapy [15] .…”
Section: Introductionmentioning
confidence: 99%
“…CTSL inhibition in drug-resistant cells not only facilitates the induction of senescence, it also prevents drug resistance [6, 7]. The upregulation of CTSL in human cancers contributes to tumor growth and survival, and to resistance of PC9 cells to the chemotherapeutic drug gefitinib [8]. Additionally, silencing CTSL can prevent the drug resistance of tumor cells, reduce the proliferation of ovarian cancer cells, weaken the cell invasion and migration properties, and increase the sensitivity of cells to paclitaxel [911].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study examined the effect of NKG2-D-activating natural killer cell receptor expression in NSCLC cells, and revealed that gefitinib attenuated NK cell-mediated cell death (27). However, the use of gefitinib may induce gefitinib-resistant NSCLC via the overexpression of cathepsin L (28). Therefore, the combination of gefitinib with other drugs may increase the killing of NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%